Estimation of serum zinc and copper levels patients with schizophrenia: a preliminary study - Santosh K Sharma; Sadhna Sood; Atul Sharma; I D Gupta (Sri Lanka Journal of Psychiatry, 2014)
Introduction: Trace elements are essential for normal metabolism. Their dysregulation adversely affects biological processes and may play a role in the pathogenesis of various diseases including schizophrenia. The role of micronutrients in schizophrenia has been investigated in a limited number of studies; the results are inconclusive. Aims: To examine the serum levels of zinc and copper in patients with schizophrenia in comparison to healthy controls and also assess these levels in the acute and chronic stage of the illness Method: The study population comprised of 150 cases and 150 age-matched controls. Their serum zinc and copper levels were measured by an Atomic Absorption Spectrophotometer. Among the cases, the stage of illness was assessed using the Positive and Negative Syndrome Scale (PANSS) score. Results: The zinc and copper levels were higher significantly in patients with schizophrenia than in the control group. Conclusion: The evaluation of zinc and copper levels in patients with schizophrenia warrants further study. DOI: http://dx.doi.org/10.4038/sljpsyc.v5i1.7076 SL J Psychiatry 2014; 5 (1): 14-17